The relationship between innovation management practices and innovation performance in the mainstream: An empirical study of Australia organisations - Terziovski, Mile (ANZAM, 2010)
The aim of this study was to examine innovation management practices of a large number of Australian companies in the manufacturing, services, computers, and construction sectors in order to determine the relationships between these practices and innovation performance in the mainstream (MIP) and new stream (NIP). Our study showed that the relationship between innovation management practice intensity explains a significant proportion of variance in MIP and NIP. Based on our findings, we conclude that innovation management practices vary between the mainstream and the new stream. Leadership commitment, innovation strategy and developing an innovation culture are the strongest predictors of innovation performance in both streams. These findings could help managers to ascertain which innovation management practices are important to create innovation-driven organisations.